2021
DOI: 10.1371/journal.pone.0244552
|View full text |Cite
|
Sign up to set email alerts
|

Rumor surveillance in support of minimally invasive tissue sampling for diagnosing the cause of child death in low-income countries: A qualitative study

Abstract: In low-and middle-income countries, determining the cause of death of any given individual is impaired by poor access to healthcare systems, resource-poor diagnostic facilities, and limited acceptance of complete diagnostic autopsies. Minimally invasive tissue sampling (MITS), an innovative post-mortem procedure based on obtaining tissue specimens using fine needle biopsies suitable for laboratory analysis, is an acceptable proxy of the complete diagnostic autopsy, and thus could reduce the uncertainty of caus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…In this study, community engagement to build stronger, sustainable relationships with the communities was adopted as a response strategy to demystify the misconceptions and rumours associated with the COVID-19 pandemic. This strategy was adopted because it has been reported as a very effective way to reduce the conceiving and spread of rumours during public health interventions [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…In this study, community engagement to build stronger, sustainable relationships with the communities was adopted as a response strategy to demystify the misconceptions and rumours associated with the COVID-19 pandemic. This strategy was adopted because it has been reported as a very effective way to reduce the conceiving and spread of rumours during public health interventions [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…These MITS enablers have been previously documented in the literature. 1,11,12,[15][16][17][18][19] Barriers to the consent process included high socioeconomic status, religious beliefs, lack of power to make decisions, and lack of trust in medics (thinking that internal organs are harvested). Previous studies have shown that some religious believers are reluctant to accept autopsy procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the optimal implementation of MITS would likely be an alternative to conventional autopsy pathology services, which are almost never exploited in most LMICs. 8 , 18 , 21 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The implementation of any postmortem procedure to determine the COD in a social setting that is not familiar with research studies, with some of the poorest health indicators and a history of myths, rumors, and negative perceptions surrounding specific public health initiatives, is marred with challenges. 18,19 It is thus evident that the success of the intervention would require an in-depth understanding of what is culturally and religiously acceptable and feasible. 11,16 Similar to what has been reported in other settings, prior to the implementation of the MITS procedure, an assessment of the foreseen acceptability of child mortality surveillance was conducted to understand attitudes and perceptions surrounding death as well as possible barriers and facilitators to the implementation of the post-mortem procedure.…”
Section: Discussionmentioning
confidence: 99%